Mobilising knowledge to improve UK health care : learning from other countries and other sectors : a multimethod mapping study /: learning from other countries and other sectors : a multimethod mapping study. (June 2015) - Davies, H. T. O; (Research fellow), Powell, Alison; Nutley, Sandra M
No abstract available